NATIONAL MASS MEDIA PARTIALITY (ANALYSIS OF LANGUAGE USE IN POLITICAL DISCOURSE) - Moh. Mukhlas; Ayunda Riska Puspita (LiNGUA: Jurnal Ilmu Bahasa dan Sastra, 2022)
A reliable newspaper should accommodate heterogeneity regarding geographical and psychological readers. The wider the coverage area of a newspaper, the more heterogeneous its readers will be. By putting more concerns on these two dimensions, a newspaper is expected to be in a neutral position. This impartiality or neutrality of the mass media becomes a more intriguing topic when it is associated with the theory arguing that language cannot be neutral since it is a form of social practice, as Halliday has always emphasized. This study aims to describe (1) the use of language (speech acts, speech targets, and speech objectives) in the political discourse contained in the editorials of Republika and Kompas newspapers and (2) the objectivity of the two newspapers. This study used a qualitative-critical approach. This type of research is descriptive-interpretative research and, more specifically, is a type of critical pragmatic analysis research. The analysis of the use of language in the editorials of Koran Republika and Koran Kompas shows that the two newspapers have different tendencies due to different ideologies. The vision and history of a newspaper can determine its ideology of a newspaper. Republika is more inclined to pair 01 (Joko Widodo-Makruf Amin) and share a similar background related to Islam. Kompas is more inclined to pair serial number 02 (Prabowo Subianto-Sandiaga Uno), one of whom is not an Islamic figure.